2019
DOI: 10.1080/07315724.2019.1691953
|View full text |Cite
|
Sign up to set email alerts
|

An 8-year Analysis of Magnesium Status in Elite International Track & Field Athletes

Abstract: Magnesium plays a critical role in athlete health and performance. It is involved in numerous physiological mechanisms that support energy production, immune function, pain modulation, muscle function and bone health. Athletes may be susceptible to magnesium deficiency due to an increased utilisation during exercise. ObjectiveThis study reports on the magnesium status of 192 Olympic and Paralympic athletes over the course of eight years. MethodsAthletes on the British Athletics world class performance plan und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…The average vMg level of the athletes in our study of 1.37 ± 0.15 mmol/l is also confirmed in the literature as 1.30 -1.34 mmol/l [23]: 1.30 ± 0.16 mmol/l (N=41), Pollock et al ( 26): 1.34 ± 0.14 mmol/l (N=192), [27]: 1.31 ± 0.39 mmol/l (N=114)], whereas in our study female athletes are significantly worse supplied with vMg than male athletes (1.33 ± 0.11 mmol/l vs 1.41 ± 0.13 mmol/l, p=0.024). This is also confirmed by the study of Pollock et al [26] [female 1.33 ± 0.06 mmol/l vs male 1.38 ± 0.04 mmol/l, p<0.05]. In this study [26], athletes with muscularity tendon injury vs athletes without muscularity tendon injury history have significantly worse vMg levels (1.31 ± 0.07 mmol/l vs 1.35 ± 0.05 mmol/l, p<0.05).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The average vMg level of the athletes in our study of 1.37 ± 0.15 mmol/l is also confirmed in the literature as 1.30 -1.34 mmol/l [23]: 1.30 ± 0.16 mmol/l (N=41), Pollock et al ( 26): 1.34 ± 0.14 mmol/l (N=192), [27]: 1.31 ± 0.39 mmol/l (N=114)], whereas in our study female athletes are significantly worse supplied with vMg than male athletes (1.33 ± 0.11 mmol/l vs 1.41 ± 0.13 mmol/l, p=0.024). This is also confirmed by the study of Pollock et al [26] [female 1.33 ± 0.06 mmol/l vs male 1.38 ± 0.04 mmol/l, p<0.05]. In this study [26], athletes with muscularity tendon injury vs athletes without muscularity tendon injury history have significantly worse vMg levels (1.31 ± 0.07 mmol/l vs 1.35 ± 0.05 mmol/l, p<0.05).…”
Section: Resultssupporting
confidence: 84%
“…This is also confirmed by the study of Pollock et al [26] [female 1.33 ± 0.06 mmol/l vs male 1.38 ± 0.04 mmol/l, p<0.05]. In this study [26], athletes with muscularity tendon injury vs athletes without muscularity tendon injury history have significantly worse vMg levels (1.31 ± 0.07 mmol/l vs 1.35 ± 0.05 mmol/l, p<0.05). Na et al (28) and Srebro et al [29] demonstrated that magnesium as an antagonist of the NMDA receptor plays an important role in the development of chronic pain as magnesium deficiency leads to amplification and upregulation of NMDA signaling and thus to tendon-muscularity pain in athletes [30].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, athletes with a history of Achilles or patella tendon pain had significantly lower magnesium levels than average. 138…”
Section: Calciummentioning
confidence: 99%
“…Decreased magnesium intake (below 400mg in men and below 310mg in women per day) is associated with lower bone density, which counts as a risk factor for stress fractures in competitive athletes [16.17]. In addition, intense anaerobic training or competition leads to increased magnesium loss in sweat and urine, resulting in magnesium deficits in up to 40% of cases (8,18,19,26). Targeted correction of proven magnesium deficiencies is significantly associated with increased muscular performance and improved cardio-vascular function in athletes [12,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%